2020
DOI: 10.1002/jso.25946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type and severity of postoperative complications on long‐term outcomes after colorectal liver metastases resection

Abstract: Background and Objectives Postoperative complications (POCs) after hepatic resection for colorectal liver metastases (CRLM) adversely affect long‐term survival. The aim of this study was to analyze the effect of POC etiology and severity on overall survival (OS) and disease‐free survival (DFS). Methods A retrospective study of 254 consecutive hepatectomies for CRLM was performed. Univariate and multivariate analyses were performed to determine the effects of demographic, tumor‐related and perioperative variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…The underlying mechanism remains to be fully elucidated, but the clinical utility of our study is still pronounced. POI occurred in 18.8% (90/479) of patients in the present study, and the incidence was consistent with previous studies (28,29) of patients who underwent abdominal surgeries. Because of its controllable and preventable nature, it is of great importance to identify the risk factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The underlying mechanism remains to be fully elucidated, but the clinical utility of our study is still pronounced. POI occurred in 18.8% (90/479) of patients in the present study, and the incidence was consistent with previous studies (28,29) of patients who underwent abdominal surgeries. Because of its controllable and preventable nature, it is of great importance to identify the risk factors.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, POI not only contributed to longer hospital stays and higher medical costs but was also associated with poor long-term outcomes of patients after surgery for various cancers. Nevertheless, only a few studies have focused on CRLM patients, and previous research is mainly limited to the effect of POI on CRLM patients who receive hepatectomy (28,29). Regardless of the severity (28), POI was proven to be associated with decreased OS and PFS in CRLM patients who underwent hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications was categorized as non-infective or infective complications, and the severity of complications was graded using the CCI and Clavien-Dindo classification. Consistent with other analyses in the literature [7,10,11], Clavien-Dindo grade ≤ II and CCI < 26.2 were grouped together. Infective complications included surgicalsite infection, urinary tract infection, respiratory infection, catheter-related bloodstream infection, and systemic sepsis.…”
Section: Patient Managementsupporting
confidence: 85%
“…A number of previous studies have shown that postoperative complications can reduce patients' long-term survival and increase the risk of disease recurrence in patients with CRLM [7][8][9][10][11]. However, the postoperative complication criteria to determine survival differ among studies.…”
Section: Introductionmentioning
confidence: 99%
“…12 In patients undergoing surgery for primary CRC, recent studies have suggested that infectious POCs 13,14 and anastomotic leaks 15 are associated with poor short-term and long-term prognosis. In patients with colorectal liver-metastasis resection, infectious POCs 16,17 have also been observed to be correlated with poor long-term prognosis. As such, it is essential to robustly and reproducibly assess POCs.…”
Section: Introductionmentioning
confidence: 99%